A balanced scorecard for measuring the impact of industry–university collaboration - Al-Ashaab, Ahmed; Flores, Myrna; Doultsinou, Athanasia; Magyar, Andrea (Taylor and Francis, 2011)
The Balanced Scorecard (BSC) can be considered as a strategic measurement tool. Many companies have applied it to measure four key aspects of their organisations’ performance: financial, customer, internal business process and learning and growth. Although it is widely used in the business arena, this original BSC was not developed to assess the impact of collaborative research projects under an open innovation strategy, where the outputs of research and development developed by collaborative projects undertaken by industry and universities should be measured in a different way. Therefore, this article will propose a scorecard to measure the outcomes of collaborative research and present two case studies of how companies are using this tool to measure the outcomes. It is important to recall that this scorecard has been developed during a collaborative research project by CEMEX Research Group AG (Switzerland) and Cranfield University (UK). During such project, a survey was developed to carry out interviews in a sample of 10 companies in UK, where it was confirmed that a collaborative BSC is a very useful tool to measure, track and improve the impact of conducting collaborative projects with universities. This article is an extended version of the one presented at the PRO-VE’09 conference (Flores et al. 2009. A balanced scorecard for measuring the impact of industry-university collaboration. In: Leveraging knowledge for innovation in collaborative networks, 10th IFIP WG 5.5 working conference on virtual enterprises, PRO-VE 2009, 7–9 October 2009, Thessaloniki, Greece, 23–32).
Keywords: balanced scorecard; open innovation; industry–university collaboration